Meningkatkan Motivasi Belajar Peserta Didik Melalui Pendekatan Pembelajaran Yang Tanggap Budaya (CRT) Pada Mata Pelajaran IPS: Increasing Students' Learning Motivation Through a Culturally Responsive Learning Approach (CRT) in Social Studies Subjects - Fitri Amanda, Yayang; Tamira, Tamira (Jurusan Pendidikan Teknik Elektro, 2025)
This research aims to improve student learning motivation through the implementation of Culturally Responsive Teaching (CRT) approach. The type of research used is Classroom Action Research (CAR). Data were collected through observation sheets and questionnaires. The subjects of this study consisted of 24 students from class VIII.2 at SMP Negeri 55 Makassar. The results indicate a significant increase in student learning motivation. Based on observation results, in the pre-cycle, only 41.6% of students were motivated, but this figure increased to 70.8% in the first cycle, and further reached 87.5% in the second cycle. Questionnaire results also showed a consistent increase, with student learning motivation recorded at 45.8% during the pre-cycle, rising to 62.5% in the first cycle, and finally reaching 79.2% in the second cycle. This emphasizes that the implementation of the Culturally Responsive Teaching (CRT) approach effectively enhances student motivation in the classroom.